Is poverty a product of environmental degradation in developing economies? A case of Pakistan - Aziz Ahmad Khan; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Amid increasing significance of the relationship between poverty and environment across nations, the study aims to scrutinize the impact of environmental pollution proxied by CO2 emission on poverty in Pakistan. It is analyzed by applying Auto Regressive Distributed Lag (ARDL) and Bounds Testing approach to time series data for the years 1976 to 2014. Findings have professed that environmental pollution has positive impact on poverty both in short-run and long-run. In control variables, GDP growth rate, education and health status in the economy have shown negative impacts on poverty. The study suggests that environmental protection policies should be applied to prevent poverty prevalence. Spread of education and health facilities are also proposed for poverty alleviation.
Keywords: 330; poverty; environment; ARDL; ECM; Pakistan